Revealing the structures of internal migration: A distance and a time-space behaviour perspectives. (December 2021) - Halás, Marián; Klapka, Pavel
Abstract: Internal migration is an important process investigated by spatial and regional sciences. When intensive, it can significantly change settlement and regional systems. The paper reveals the structures of internal migration based particularly on distance of movements and partly on their motivations. In order to distinguish between short and long distance migration based on informed decision and not on ad hoc threshold (estimate) we employ (i) the concept of the time geography as behavioural framework, (ii) the concept of daily urban (spatial) systems as spatial framework, and (iii) the concept of (sub)urbanisation as theoretical framework. The results are based on the combination of these three concepts, together with the quantitative analysis of statistically recorded internal migration in the Czech Republic (length of movements and their motivations). The daily urban system of the city of Olomouc (the Czech Republic) is further analysed using the time geographic approach and time use diaries of individuals. The analysis of internal migration in the Czech Republic showed us that short distance migration was defined by 50 km upper distance limit, by other motivations than employment, by intra-regional rather than inter-regional flows, and by the existence of areal overlap of activity time spaces before and after the move was completed. Patterns of time-space behaviour for urban and rural (suburban) population sample in the daily urban system of Olomouc have been generalised and two basic types of time space existence of individuals identified: radial for urban population and circular for rural (suburban) population. Highlights: We relate internal migration to the concept of time geography. We relate internal migration to the concept of daily urban (spatial) systems. We propose several alternatives to distinguish between short and long distance migration.